Production of deuterons, tritons, ³He nuclei, and their antinuclei in pp collisions at √s =0.9, 2.76, and 7 TeV - Acharya, S.; Adam, J.; Adamovã, D.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, N.; Ahn, S.U.; Aiola, S.; et al. (American Physical Society, 2018)
Invariant differential yields of deuterons and antideuterons in pp collisions at √s = 0.9, 2.76 and 7 TeV and the yields of tritons, ³He nuclei, and their antinuclei at √s = 7 TeV have been measured with the ALICE detector at the CERN Large Hadron Collider. The measurements cover a wide transverse momentum (Pᴛ) range in the rapidity interval |y| < 0.5, extending both the energy and the Pᴛ reach of previous measurements up to 3 GeV/c for A = 2 and 6 GeV/c for A = 3. The coalescence parameters of (anti)deuterons and 3He nuclei exhibit an increasing trend with Pᴛ and are found to be compatible with measurements in pA collisions at low Pᴛ and lower energies. The integrated yields decrease by a factor of about 1000 for each increase of the mass number with one (anti)nucleon. Furthermore, the deuteron-to-proton ratio is reported as a function of the average charged particle multiplicity at different center-of-mass energies.
Keywords: Physics; Deuterium; Nuclear physics; Nucleon; Hadron; Large Hadron Collider; Particle physics; https://purl.org/pe-repo/ocde/ford#1.03.04